2011
DOI: 10.3168/jds.2010-3923
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intensified feeding of heifer calves on growth, pubertal age, calving age, milk yield, and economics

Abstract: The objective of this study was to determine if increasing the energy and protein intake of heifer calves would affect growth rates, age at puberty, age at calving, and first lactation milk yield. A second objective was to perform an economic analysis of this feeding program using feed costs, number of nonproductive days, and milk yield data. Holstein heifer calves born at the Michigan State Dairy Cattle Teaching and Research Center were randomly assigned to 1 of 2 dietary treatments (n=40/treatment) that cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
119
6
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(146 citation statements)
references
References 17 publications
16
119
6
5
Order By: Relevance
“…The puberty weights obtained in this experiment are close to those reported by Samadi et al (2014), in which the authors found values of approximately 357 kg in Brahman heifers. Rincker et al (2011) subjected dairy heifers at an ADG of 0.95 kg during 180 days before the date predicted for puberty and observed puberty at 270 days. The accumulated weight gain at eleven months of age from the different genotypes had not been sufficient to show their development potential in body weight.…”
Section: Discussionmentioning
confidence: 99%
“…The puberty weights obtained in this experiment are close to those reported by Samadi et al (2014), in which the authors found values of approximately 357 kg in Brahman heifers. Rincker et al (2011) subjected dairy heifers at an ADG of 0.95 kg during 180 days before the date predicted for puberty and observed puberty at 270 days. The accumulated weight gain at eleven months of age from the different genotypes had not been sufficient to show their development potential in body weight.…”
Section: Discussionmentioning
confidence: 99%
“…The animals with the fastest growth rate produced lower 305-day milk yields in their first lactation compared with the slowest growth (9387 v. 9873 kg). Another trial by Davis Rincker et al (2011) found that pre-weaned heifers provided with a higher energy and protein diet did not alter their energy-corrected, ageuncorrected 305-day milk yield in comparison with those fed a conventional diet (averaging 10 069 and 9778 kg, respectively) although this difference became significant when the genetic values of the heifers were taken into account. Similarly, Soberon et al (2012) reported that for every 1 kg increase in ADG during the pre-weaning period, first lactation milk yield increased by 850 and 1113 kg in two different herds studied, showing a consistent positive effect of good early growth on subsequent milk production.…”
Section: Milk Productionmentioning
confidence: 99%
“…Feeding whole milk or milk replacer to support rapid pre-weaning growth rates enables heifers to achieve breeding size earlier. For example, calves with an ADG of 0.8 kg/day pre-weaning calved 27.5 days earlier than calves fed for gains of 0.55 kg/day (RaethKnight et al, 2009) while heifers fed for a pre-weaning ADG of 0.64 kg/day conceived and calved at a younger age when bred at the same BW as calves with growth rates of 0.44 kg/day (Davis Rincker et al, 2011). Shamay et al (2005) fed more milk pre-weaning and compared whole milk with milk replacer.…”
Section: Nutrition and Growth Ratementioning
confidence: 99%
“…The decision to feed a restricted or enhanced feeding programme not only has financial implications, but also affects feed efficiency and growth [8]. Studies examining intensified feeding programmes have found that heifers attain puberty, conceive and calve earlier, and produce more milk during their first lactation than heifers fed conventional feeding programmes [9]. Heinrichs and Heinrichs [10] also showed that a 1 kg increase in dry matter intake (DMI) at weaning produced a 286.7 kg increase in first lactation milk yield and that the age at which calves began to consume >900 g/day was associated with an increased lifetime production of milk and milk constituents.…”
Section: Introductionmentioning
confidence: 99%